Sustainable Energy Efficiency Implementation in Building - Nidzamuddeen, Ishak; Abdalla, Ahmed N.; Noraziah, Ahmad (2012)
Energy efficiency and green technology are common terms been discussed in engineering world today with the aim to achieve a low-carbon society. In Malaysia, these two terms were boost up when the government starts to implement the National Green Technology Policy pioneered by Ministry of Energy, Green Technology and Water starts by the year of 2009. Different area needs different approach of energy efficiency, without compromising the comfort level of the user. In focusing the implementation of energy efficiency in building, this research will discuss different measures starting from the simplest measures such as awareness program up to smart method which include hardware control and user interface. Smart energy efficiency measures will combine the use of control device, sensors, fast communication medium and GUI which will enable user access, monitor and control. This research will also look on the wireless as a communication medium in order to enhance the process of control and monitoring.